The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1007/s12010-013-0133-2
|View full text |Cite
|
Sign up to set email alerts
|

Stimulatory Effect of Different Lignocellulosic Materials for Phenolic Compound Production and Antioxidant Activity from Inonotus obliquus in Submerged Fermentation

Abstract: White-rot fungus Inonotus obliquus grown in submerged culture produces antioxidative phenolic compounds. In this study, addition of lignocellulosic materials into the liquid culture increased the production and antioxidant activity of extra- and intra-cellular phenolic compounds (EPC and IPC, respectively). The production of EPC and IPC was significantly enhanced by wheat straw (by 151.2 and 45.3 %), sugarcane bagasse (by 106.9 and 26.1 %), and rice straw (by 67.6 and 38.9 %). Both of the EPC and IPC extracts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 24 publications
3
13
0
Order By: Relevance
“…However, it should be noted that phenolic compounds obtained via chemical methods would have fewer applications in the food and pharmaceutical industries than those obtained via biological methods. Therefore, the possibility of the use of phenolic compounds as antimicrobial agents was investigated [ 35 , 36 ]. Moreover, phenolic compounds could be used as biological pesticides because they could be produced in large quantities due to the huge amounts of available rice straw.…”
Section: Resultsmentioning
confidence: 99%
“…However, it should be noted that phenolic compounds obtained via chemical methods would have fewer applications in the food and pharmaceutical industries than those obtained via biological methods. Therefore, the possibility of the use of phenolic compounds as antimicrobial agents was investigated [ 35 , 36 ]. Moreover, phenolic compounds could be used as biological pesticides because they could be produced in large quantities due to the huge amounts of available rice straw.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, a great demand for the sclerotia of I. obliquus is observed because of several characteristics, such as rarity in nature, and complex cultivation. Submerged fermentation of I. obliquus has received great attention and perceived as a promising alternative for efficient production of mycelial biomass, phenolic compound, and exopolysaccharides (18,19). However, I. obliquus in submerged culture accumulates less bioactive metabolites than those grow in natural habitats (20).…”
Section: Discussionmentioning
confidence: 99%
“…However, I. obliquus in submerged culture accumulates less bioactive metabolites than those grow in natural habitats (20). To accelerate the production of metabolites by I. obliquus, effect of different lignocellulosic materials have been studied (18,21). Other studies also reported that the extracts from host-related species can stimulate mycelial biomass and metabolite production of medicinal mushroom such as Ganoderma lucidum (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Submerged fermentation provides a number of potential advantages, for instance a greater mycelial biomass and secondary metabolite production in a more‐compact space over a shorter time with a lower chance of contamination, availability of convenient control, and easy fermentation processing . Many investigators have verified optimal medium contribute to the flavonoid production by submerged fermentation . Additionally, the secondary metabolites products were obtained from liquid submerged fermentation and exhibited almost the same biological activities as those of fruiting body .…”
Section: Introductionmentioning
confidence: 98%